Isoprenoids responsible for protein prenylation modulate the biological effects of statins on pancreatic cancer cells - Gbelcová, Helena; Rimpelová, Silvie; Knejzlík, Zdeněk; Šáchová, Jana; Kolář, Michal; Strnad, Hynek; Repiská, Vanda; D'Acunto, Walter Cosimo; Ruml, Tomáš; Vítek, Libor (Lipids in health and disease, 2017)
BACKGROUND: Statin treatment of hypercholesterolemia is accompanied also with depletion of the mevalonate intermediates, including farnesyl pyrophosphate (FPP) and geranylgeranyl pyrophosphate (GGPP) necessary for proper function of small GTPases. These include Ras proteins, prevalently mutated in pancreatic cancer. In our study, we evaluated the effect of three key intermediates of the mevalonate pathway on GFP-K-Ras protein localization and the gene expression profile in pancreatic cancer cells after exposure to individual statins. METHODS: These effects were tested on MiaPaCa-2 human pancreatic cancer cells carrying a K-Ras activating mutation (G12C) after exposure to individual statins (20 μM). The effect of statins (atorvastatin, lovastatin, simvastatin, fluvastatin, cerivastatin, rosuvastatin, and pitavastatin) and mevalonate intermediates on GFP-K-Ras protein translocation was analyzed using fluorescence microscopy. The changes in gene expression induced in MiaPaCa-2 cells treated with simvastatin, FPP, GGPP, and their combinations with simvastatin were examined by whole genome DNA microarray analysis. RESULTS: All tested statins efficiently inhibited K-Ras protein trafficking from cytoplasm to the cell membrane of the MiaPaCa-2 cells. The inhibitory effect of statins on GFP-K-Ras protein trafficking was partially prevented by addition of any of the mevalonate pathway's intermediates tested. Expressions of genes involved in metabolic and signaling pathways modulated by simvastatin treatment was normalized by the concurrent addition of FPP or GGPP. K-Ras protein trafficking within the pancreatic cancer cells is effectively inhibited by the majority of statins; the inhibition is eliminated by isoprenoid intermediates of the mevalonate pathway. CONCLUSIONS: Our data indicate that the anticancer effects of statins observed in numerous studies to a large extent are mediated through isoprenoid intermediates of the mevalonate pathway, as they influence expression of genes involved in multiple intracellular pathways.
Keywords: Protein Prenylation; prenylace proteinů; signální transdukce; transport proteinů; Statins; Mutation; protoonkogenní proteiny p21(ras); atorvastatin; Farnesyl pyrophosphate; rekombinantní fúzní proteiny; Gene Expression Regulation; Proto-Oncogene Proteins p21(ras); Sesquiterpenes; kyselina mevalonová; stanovení celkové genové exprese; lovastatin; polyisoprenylfosfáty; Humans; lidé; Isoprenoids; mikročipová analýza; Microarray Analysis; kyseliny mastné mononenasycené; Gene Expression Profiling; Fluvastatin; Indoles; fluvastatin; beta-buňky; Pancreatic cancer; Fatty Acids, Monounsaturated; Mevalonate; Lovastatin; anticholesteremika; Atorvastatin; Anticholesteremic Agents; simvastatin; Simvastatin; Insulin-Secreting Cells; mutace; K-Ras oncogene; Mevalonic Acid; indoly; Protein Transport; nádorové buněčné linie; seskviterpeny; Cell Line, Tumor; Polyisoprenyl Phosphates; Geranylgeranyl pyrophosphate; HMG-CoA reductase inhibitors; Recombinant Fusion Proteins; Gene expression; Green Fluorescent Proteins; Signal Transduction; regulace genové exprese; Prenylation; zelené fluorescenční proteiny